Numerals in Kokborok - Debbarma, Dr. Biman (International Journal of Language, Literature and Culture, 2022)
This paper will describe the numerals used in the Kokborok language. Kokborok belongs to the Bodo-Garo sub-group of the Tibeto-Burman language family, spoken in the Northeastern state of Tripura, India. According to the 2011 census, the Kokborok speakers' total population is around 8,80,537 (23.97% of the total population). This language happens to be one of the lingua-franca among the tribes. The numerals in Kokborok are of decimal type, i.e., ten base and purely absent of vigesimal, i.e., twenty base. Structurally, Kokborok categorizes into six numerals viz., (i) cardinals, (ii) ordinals, (iii) multiplicative, (iv) fractional, (v) distributive, and (vi) restrictive numerals. The raw numbers from one to ten are the basic numerals used as compounding for forming higher numerals by addition or multiplication. Syntactically, in compound nouns, the numeral always follows the head noun in Kokborok.